(untitled) (Research, Society and Development, 2022)
Skin wounds directly affect the quality of life of populations, generating complications and high costs in public health, with this, researchers look to natural products for alternatives to improve health care based on ethnopharmacology. To evaluate the healing potential of Moringa oleifera (Lam.) And Maythenus ilicifolia (Mart.) Ex Reiss in lesions of Swiss mice. To prepare the formulation, the hydroalcoholic extract of the leaves of the moringa and the espinheira santa was obtained through a process of dynamic maceration. In the experiment, 40 mice were used, distributed in four groups of ten animals each (n = 10): GCP- Positive Control Group using Fibrinase®, GCN- Negative Control Group using the base cream without extract, GT-MI- Maythenus Treatment Group Ilicifolia and GT-MO Moringa oil treatment group. The results demonstrate good clinical evolution in all groups; in the macroscopic evolution, the treatment groups presented a dense fibrinoleucocyte crust that were present in some animals until the second half of the research, without influencing the tissue repair process; the GCP showed good healing evolution until the end of the tests; the GCN expressed events that meet healing, such as edema, exudation and ulcerative process. The treatment groups expressed a satisfactory percentage of edge contraction compared to the GCP. Thus, the results explained demonstrate that the topical treatment of the aforementioned species at 10% effectively contributes to healing, contributing in all stages to accelerate and prevent possible external interferences in the tissue repair of experimental excisional wounds.